PENCIPTAAN NILAI TAMBAH DAN PENGEMBANGAN AGROINDUSTRI BERBASIS KOMODITAS KELOR (Moringa Olifiera) - Soetriono Soetriono; Djoko Soejono; Dimas Bastara Zahrosa; Ariq Dewi Maharani (University of Jember, 2019)
The Banyuwangi Regency area has the opportunity and has the potential to develop Moringa commodities. Moringa commodity enthusiasts in Banyuwangi Regency from various circles, both industry, medicine and vegetables are eaten. This study is to determine the added value The Banyuwangi Regency area has the opportunity and has the potential to develop Moringa commodities. Moringa commodity enthusiasts in Banyuwangi Regency from various circles, both industry, medicine and vegetables are eaten. This study is to determine the value added and economics of Moringa commodities and the strategy of developing Moringa commodity agroindustry. The method of data analysis uses descriptive, income analysis, value added analysis, and FFA (Force Field Analysis). The results obtained from Moringa processed products have a value-added advantage per 1 kg of positive raw material. Revenue per 1 production process, Moringa powder Rp. 2,943,263.89, Ginger Moringa teabag Rp. 1,210,463.89, Moringa dye jasmine tea Rp. 857,183.89, Moringa teabag Rp. 206,563.89, Moringa noodles amounting to Rp 104,255.56, moringa tortillas amounting to Rp 58,755.56, and lemuru kelor tortillas at Rp 177,055.56. The development strategy is to develop the cultivation of Moringa commodities intensively in order to ensure the continuity of raw materials for agro-industries and develop a plasma core partnership pattern with farmers to ensure the availability of raw materials for agro-industries; and optimizing the use of yield processing technology to maximize production capacity maximally while taking into account market demand.